Educators Creating Liberatory and Inclusive Environments using Contemplative Educational Tools - Julee Rosser (Adult Education Research Conference, 2024)
Contemplative educational tools can enhance opportunities for adult educators to develop student-centered, liberatory education, helping students to learn through their triggers, thus creating transformative learning experiences.
Keywords: mindfulness; contemplative education